A case of acute progressive diffuse interstitial lung disease preceding idiopathic multicentric Castleman disease. (2020) - Nabeya, Daijiro; Yoshimatsu, Yuki; Fujiwara, Hiroshi
Abstract: It has been considered that idiopathic multicentric Castleman disease often involves pulmonary complications recognized as lymphocytic interstitial pneumonia. On the other hand, recent reports show that the computed tomography often show diffuse interstitial lung disease inconsistence with lymphocytic interstitial pneumonia. Pulmonary diseases with idiopathic multicentric Castleman disease are still rare and poorly understood. Here, we report a case of acute progressive diffuse interstitial lung disease, diagnosed as non-specific interstitial pneumonia, preceding idiopathic multicentric Castleman disease. A 65-year-old male visited our outpatient clinic for dyspnea on exertion. Imaging tests revealed interstitial lung disease showing non-specific interstitial pneumonia pattern, pulmonary function test proved the decline of vital capacity and laboratory tests showed increased fibrosis biomarkers; therefore, initially, he had been diagnosed as non-specific interstitial pneumonia. However, imaging tests also showed mediastinum lymphadenopathy, and laboratory tests revealed increased interleukin-6. Idiopathic multicentric Castleman disease was suspected. The lung and mediastinum lymph node biopsies were performed, and pathological findings of the lymph nodes were compatible with multicentric Castleman disease. Pathological findings of the lung showed that the fibrous thickening of interstitium and the collapse of alveoli. We diagnosed this case as idiopathic multicentric Castleman disease preceded by diffuse interstitial lung disease. Treatment with prednisolone improved the dyspnea, and the pulmonary lesions disappeared. The presented case suggests that interstitial lung disease could precede idiopathic multicentric Castleman disease. Chest physicians should be aware that idiopathic multicentric Castleman disease is one of the causative diseases of diffuse interstitial lung disease like non-specific interstitial pneumonia on the chest images.